Design and Build Data Transfer Process Security on File Transfer Protocol (Ftp) Servers Using Transport Layer Security (Tls) Protocol - Boy Rizky Akbar; Muhammad Iqbal; Arpan (Jurnal Mantik, 2022)
Attacks on computer network security are very common, crimes in cyberspace are often carried out by someone and even a group of people who want to penetrate a security data on a network. This activity aims to search, damage, modify, steal and even obtain information or data on the network, one of which is Packet Sniffer attacks. This method is done by monitoring or analyzing data packets that are transmitted from the client computer to the server computer through a computer network. File Transfer Protocol (FTP) is still a reference as a medium used to transfer data with a fast process of uploading and downloading from server to client so that data is more secure, and on FTP Server security.